Forhandlinger ved Lolland-Falsters Forstmandsforenings Møde den 1. Maj 1872. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Forhandlinger ved Lolland-Falsters Forstmandsforenings Møde den 1. Maj 1872.